Picturing the beautiful game - Haxall, Daniel (Bloomsbury Visual Arts, 2019)
From the Oval to the Crystal Palace : the FA Cup Final and its depiction in the Victorian illustrated press / Alexander Leese – The footballer as the figure of the new man in Italian and Russian avant-garde, 1910s-1930s / Przemysław Strożek – Imagining reality : critical responses to the commercialization of the beautiful game / Ray Physick
Includes bibliographical references and index
Keywords: Soccer in art; Soccer in popular culture